PENGARUH PENDIDIKAN KEPRAMUKAAN DALAM PEMBENTUKAN KARAKTER SISWA DI MTs. ALKHAIRAAT KALUKUBULA - Mahmud, Mahmud (Katalogis, 2017)
Formulation of the problem in this research is: "Is the scouting educational influence on the character formation of students in MTs. Alkhairaat Kalukubula? ". While the purpose of this study was to determine and analyze the effect on the formation of character scouting education students in MTs. Alkhairaat Kalukubula. This research is a descriptive study causal approach used surveys. The research sample as many as 52 students at MTs Alkhairaat Kalukubula using census where all the population sampled so that all members and scoutmaster who exercise regularly scouting in MTs Alkhairaat Kalukubula set as the primary data source research. Data were analyzed using simple linear regression analysis with the results showed that the educational scouting has an influence on the character formation of students in MTs. Alkhairaat Kalukubula. It is based on the results of statistical tests test-t, where t-count value is greater than t-table (7.474> 2.021) and a probability of 0.000 at significant level of 95% smaller than a 0.05 (p <0, 05). Means that Ho refused and Hi accepted.